Exploring Catholic Literature: A Companion and Resource Guide - Reichardt, Mary R. (Rowman & Littlefield Publishers, 2003)
Designed for students of all ages, Exploring Catholic Literature: A Companion and Resource Guide provides an engaging and succinct introduction to twelve recognized masterpieces of Catholic literature, from Augustine's 4th century conversion narrative, The Confessions, to the recent poetry of Denise Levertov collected in The Stream and the Sapphire. Each chapter contains a brief biography of the author, an extended critical essay highlighting the work's Catholic and literary aspects, suggestions for further reading and study, and questions for discussion.